Camellia sinensis mediated synthesis of zero valent iron nanoparticles and study of their efficacy in dye degradation and antibacterial activity. Issue 18 (28th December 2022) - Das, Jayanta; Dhar, Siddhartha Sankar
ABSTRACT: In this work highly amorphous zero valent iron (ZVI) nanoparticles (NPs) were synthesised using young shoots of Camellia sinensis . Polyphenol-coated ZVI NPs were characterised using Ultraviolet-visible (UV-Vis) spectroscopy, Fourier-transform infrared (FTIR) spectroscopy, X-rays diffraction (XRD) spectroscopy, Scanning electron microscope (SEM) and Transmission electron microscope (TEM). Particles obtained were a mixture of spherical and quasi-spherical shapes with an average size of 74 nm. Application of green synthesised ZVI NPs as Photo-Fenton like catalyst showed 100% degradation of Rhodamine B within 60 minutes. The kinetics of the degradation strictly followed pseudo-first-order reaction with rate constant 0.1 min −1 . ZVI NPs were also investigated for their antibacterial potency using disc diffusion method against four different bacterial strains. Out of four bacterial strains viz. Enterococcus faecalis, Staphylococcus aureus, Escherichia coli and Pseudomonas aeruginosa, ZVI NPs (10 mg/ml) were found to be most potent against Pseudomonas aeruginosa where the zone of inhibition is found to be 18.4 mm.